2018
DOI: 10.1016/j.stemcr.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MECP2 Leads to Activation of P53 and Neuronal Senescence

Abstract: SummaryTo determine the role for mutations of MECP2 in Rett syndrome, we generated isogenic lines of human induced pluripotent stem cells, neural progenitor cells, and neurons from patient fibroblasts with and without MECP2 expression in an attempt to recapitulate disease phenotypes in vitro. Molecular profiling uncovered neuronal-specific gene expression changes, including induction of a senescence-associated secretory phenotype (SASP) program. Patient-derived neurons made without MECP2 showed signs of stress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 42 publications
5
64
0
Order By: Relevance
“…The fusion organoid system is highly amenable to such detailed cellular and circuit analyses and provides unprecedented opportunities for modeling neural network dysfunction associated with a variety of human neurological disorders. and ganglionic eminence (GE) organoids were generated from the H9 hPSC line 41 or Rett hiPSCs 30 as described previously 15 Following initial imaging in the absence of drugs, organoids were then subjected to 1-minute incubation with the GABAA receptor antagonist gabazine (25 µM) or bicuculline methiodide (100 µM) and the identical fields were re-imaged after drug exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fusion organoid system is highly amenable to such detailed cellular and circuit analyses and provides unprecedented opportunities for modeling neural network dysfunction associated with a variety of human neurological disorders. and ganglionic eminence (GE) organoids were generated from the H9 hPSC line 41 or Rett hiPSCs 30 as described previously 15 Following initial imaging in the absence of drugs, organoids were then subjected to 1-minute incubation with the GABAA receptor antagonist gabazine (25 µM) or bicuculline methiodide (100 µM) and the identical fields were re-imaged after drug exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent hiPSC-based study has suggested that Rett may impact prenatal neurogenesis through microRNA-mediated changes in AKT and ERK activity 26 . Interestingly, while neuroanatomical changes in dendritic arborization and spine density have been reported in multiple Rett models 25,[27][28][29][30] , gross structural abnormalities are less prevalent.…”
Section: Rett Syndrome Fusion Organoids Exhibit Hypersynchronous Neurmentioning
confidence: 99%
“…In the aging rat brain, p53 is upregulated compared to young animals [23]. Moreover, in hiPSCs-derived neurons carrying a loss-of-function mutation of the MECP2 gene causing intellectual disability (Rett syndrome), the mutation-associated induction of p53 is associated with a senescence-like phenotype directly in neurons [24]. With further support, p53 is required for the manifestation of hyperinsulinemia-triggered senescence in terminally differentiated adipocytes [7].…”
Section: Atypical Neuronal Cell Cycle Activity and Pseudomitosenescencementioning
confidence: 94%
“…Along with functional changes, aged cortical neurons showed alterations in molecular hallmarks associated with neuronal senescence [45][46][47] . We found that aged neurons exhibit higher expression levels of p53 and increased activation of pJNK and pP38, three molecules implicated in neuronal demise 48,49 .…”
Section: Age-related Functional and Molecular Changes On Cultured Cormentioning
confidence: 99%